2021
DOI: 10.1007/s11356-021-16638-9
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of green supply chain management: a close-up study

Abstract: Green supply chain management (GSCM) is an important part of most production organisations in developed countries. Meanwhile, developing countries are yet to fully embrace the concept. This study, therefore, investigated the drivers of GSCM using a close-up approach in a leading manufacturing organisation in Nigeria with sustainability initiatives. One hundred and fty-four questionnaires retrieved from the supply chain management team of the organisation were subjected to descriptive and inferential statistics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 102 publications
0
18
0
Order By: Relevance
“…The survey found that current research on the role of law in promoting sustainable green growth through the use of political institutions is incomplete. Therefore, this paper presents a study of the role of law in the use of political institutions to promote sustainable green growth [ 13 , 14 ]. This paper applies a logistic regression model to the analysis of the role of law in the use of political institutions to promote sustainable green growth and proposes a new model for use in the analysis of the role of law in promoting green growth.…”
Section: Methodsmentioning
confidence: 99%
“…The survey found that current research on the role of law in promoting sustainable green growth through the use of political institutions is incomplete. Therefore, this paper presents a study of the role of law in the use of political institutions to promote sustainable green growth [ 13 , 14 ]. This paper applies a logistic regression model to the analysis of the role of law in the use of political institutions to promote sustainable green growth and proposes a new model for use in the analysis of the role of law in promoting green growth.…”
Section: Methodsmentioning
confidence: 99%
“…Green Supply Chain Management (GSCM) is an approach that integrates environmental, social, and economic issues. Several companies have successfully implemented GSCM practices [51][52][53][54][55]. For example, Walmart has implemented GSCM practices to reduce waste, improve energy efficiency, and promote sustainable sourcing [51].…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…Nike has implemented GSCM practices to reduce carbon emissions, improve labor conditions, and promote sustainable material sourcing [52]. Toyota has implemented GSCM practices to reduce waste, improve energy efficiency, and promote sustainable material sourcing [53]. Other companies that have successfully implemented GSCM practices include Coca-Cola, Dell, and Unilever [54,55].…”
Section: Green Supply Chain Managementmentioning
confidence: 99%
“…In contrast, Khodaparasti et al argued that customer pressure is not significantly related to green purchasing and that environmental concerns, employee competencies, motivations, and rewards positively influence firms' green purchasing practices [ 57 ]. Besides, an empirical study by Ososanmi et al showed that close collaboration between governments and other organizations and individuals can promote green supply chain practices in developing countries and that training can enhance awareness of sustainable development [ 58 ].…”
Section: Literature Reviewmentioning
confidence: 99%